Enhancement of the local inflammatory response to bacterial infection by muramyl dipeptide. - Lamont, P. M. (1984)
The effect of the synthetic immuno-adjuvant compound, muramyl dipeptide (MDP), upon the local inflammatory response to experimental bacterial infection was assessed by histological examination. Within 24 h of the insertion of a bacteria-laden suture into the medial thigh musculature of mice treated with either MDP or placebo, an enhanced degree of polymorphonuclear leucocyte infiltration in the muscle around the suture was observed in the MDP-treated animals. The inflammatory response around a sterile suture was less intense in both treatment groups and specific correlation between the degree of local inflammation and the extent of bacteraemia developing in either group of animals was not noted. The extent of bacteraemia developing in either group of animals was not noted. The previously observed protection conferred by MDP against the local impact of bacterial challenge appears to be mediated in part by enhancement of the acute local inflammatory response.